Еstrogen receptor α (ESR1) and SRC family kinase (LYN) gene's mutations associated with ovarian cancer endocrine therapy resistance - E. A. Shestakova (Успехи молекулярной онкологии)
Recently multiple data accumulated concerning mutations in the ESR1 gene coding estrogen receptor α (mutESR1) and in the LYN gene coding non receptor tyrosine kinase SRC family member (mutLYN) that are associated with endocrine therapy resistance and that could be considered as markers of endocrine therapy efficiency. In case of gynecologic cancers including ovarian cancer the most frequent mutESR1 are ESR1L536H/P/R/V , ESR1Y537S/N/C/H, ESR1D538G that emerge in the course of hormonotherapy especially using aromatase inhibitors. mutLYN including LYNE159K, LYND189Y, LYNK209N, LYNA370T, LYNG418R, LYNA503D are also identified. mutESR1 and mutLYN increase transcriptional activity of estrogen receptor α (ERα) coded with ESR1 gene and catalytic activity of LYN kinase inducing endocrine therapy resistance. Interdependence of ESR1 and LYN genes is revealed at the level of proteins that they code as the kinases of the SRC family including LYN activate ERα-dependent transcription due to the phosphorylation of ERα at Y537 amino-acid residue that is the most frequently mutated in tumors with endocrine therapy resistance. The aim of the review is revealing the clinical correlations of mutESR1 and mutLYN with the ovarian cancer endocrine therapy resistance that opens perspectives of mutESR1 and mutLYN use as new predictive markers of ovarian cancer and development of more efficient anti-tumor medicaments. In the review the information obtained from PubMed database for the last 20 years using the following key words: ESR1, LYN, mutation(s), estrogen receptor α (ERα), LYN kinase, SRC family kinases, ovarian cancer, gynecologic(al) cancer is discussed.